Carbon emissions comparison in modular and site-built residential construction - Kouhirostami, Maryam; Chini, Abdol R. (Modular and Offsite Construction (MOC) Summit Proceedings, 2022)
The construction industry has significant environmental impacts by consuming natural resources, emitting greenhouse gas (GHG), and generating wastes. Hence, lowering the environmental impacts of residential buildings deserve serious attention. Over the past decades, Modular construction has gained popularity as an address to that problem due to its advantages: lower cost, lower waste, higher productivity, faster construction time, and lower environmental impacts. This prefabrication technique also provides mass production specifically to address the housing crisis. In addition, lower carbon emission of modular construction makes it even more popular in residential sector. This study aims to review literature on environmental impacts of modular residential construction and their comparison with equivalent site-built homes using the life cycle assessment method (LCA). The goal is to identify the gaps in existing knowledge and suggest research opportunities for future study. The results indicate lack of comprehensive LCA framework to study the environmental impacts of modular and site-built construction. The findings recommend developing a comprehensive LCA framework for the comparison.